IMPROVEMENT OF LOGISTICS CHAIN MANAGEMENT PROCESSES IN THE CONSTRUCTION FIELD - Mirsodikov Abdulla (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In our country, optimization of costs and improvement of management processes in the construction industry, including the logistics chain, diversification of enterprises and diversification of production and service processes, increasing the economic potential of enterprises through the full formation of value chains in the industry, thereby ensuring employment , great attention is paid to meeting the needs of the population in construction products and improving their welfare.